The African Continental Free Trade Area and its Employment-generation Pontentials in Nigeria's Industrial Sector - Oziengbe Scott Aigheyisi (Economy, Business and Development: An International Journal (EB&D), 2021)
The study empirically examines the employment generation potentials of the African Continental Free Trade Area (AfCFTA) in Nigeria's industrial sector. The ARDL approach to cointegration and error correction modeling is employed for analysis of annual time series data covering the period 1991-2020. The study finds inter alia that the short run effect of expansion of intra-African trade (expected to result from the AfCFTA) on industrial sector employment is positive and statistically significant. The long run effect is also positive, but not statistically significant. It also finds that trade openness - deeper integration of the economy with the global market - significantly enhances employment generation in the nation's industrial sector in the long run; though the short run effect is negative and significant. These suggest that the country's membership of the AfCFTA and implementation of policies to (cautiously) deepen the integration of the economy with the global market should be considered as supplementary avenues to achieving sustainable employment generation in the nation's industrial sector in the short-and long-run. Other evidence-based policy recommendations are discussed.
Keywords: E24; F13; F14; F15; L60; 330; African Continental Free Trade Area; Intra-African Trade; Global Trade; Industrial Sector; Em ployment; Unemployment